Common features of chromatin in aging and cancer - Cause or Coincidence? - Zane, Linda (Trends Cell Biol, 2014)
Age is a major risk factor for cancer. Alterations in DNA methylation, histone modifications, chromatin structure and epigenetic regulatory mechanisms are prominent hallmarks of both the aging process and of cancer. Intriguingly – or possibly coincidentally - several chromatin features are common between aging and cancer. Here we ask whether, and if so how, aging-associated chromatin modifications contribute to tumor susceptibility and tumorigenesis.